Transactional leadership for implementing a green campus: Driving sustainable change through effective leadership strategies - Sulistiani, Dwi; Hasanah, Ma’rifatul; Cholifah, Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This paper explores the role of transactional leadership in implementing green campus initiatives, as long as the strategy, challenge and limitations. As higher education institutions face growing pressure to adopt sustainable practices, effective leadership is paramount. Qualitative research with a case study approach was used to answer research questions. The data in this research is in the form of interviews and documentation at Islamic state universities in Indonesia with the best green campus. Transactional leadership, focusing on clear objectives, rewards, and performance-based management, offers a structured approach to achieving campus environmental sustainability. This paper examines how transactional leadership can be utilized to drive the adoption of green policies, engage stakeholders, and achieve measurable environmental outcomes. One of the key strengths of transactional leadership in green campus initiatives is its ability to provide structure and clarity. Stakeholder participation in green campus initiatives can be encouraged by transactional leadership's emphasis on incentives and rewards. The implementation of green campus projects is greatly aided by transactional leadership, which offers structure, direction, and motivation through rewards and incentives. Higher education institutions must have certain strategies: leadership and vision, stakeholder engangement and collaboration, sustainable education and training, as long as monitoring and evaluation to succeed green campus. However, there are several challenges and limitations to implementing a green campus, such as: budgetary limitaions, infrastructure and technological constraints, cultural and behavioral opposition, complexity and multidisciplinary collaboration, measurement and accountability, managing conflicting priorities, policy and regulatory challenges.